Kleines Woerterbuch der Kirchenslavischen Sprache Wortschatz der gebraeuchlichsten liturgischen Texte mit deutscher Uebersetzung; Dritte, neu bearbeitete und erweiterte Auflage. - Deschler, Jean-Paul (Slavistische Beitraege, 2003)
The book contains the vocabulary of the main liturgical texts of the Byzantine rite, d. H. Hesperinos, the Orthros, the liturgies and the Gospels; the remaining Old and New Testament writings are taken into account, as far as they are used on Sundays and higher festivals. This "basic vocabulary" should now make it possible to easily translate such texts in modern (Russian) church Slavic spelling. The dictionary, a vastly expanded edition of the previous edition, which has been out of print for years, seeks to make linguistic and theological knowledge useful for practical needs: it helps the Slavic student and those interested in the Eastern Church as well as the icon-lover or art historian without Russian or Serbian knowledge, biblical and to understand liturgical texts in the form of Modern Russian-Church Slavonic. Of benefit are the grammatical and orthographic references in the introduction, the references of certain forms of inflection to the initial forms in the dictionary and the appendix with abbreviations in manuscripts and prints as well as icons. Another directory contains person and place names from the biblical books, the saints' calendar, and the secular history found in liturgical texts and icons, with orthographic variants or misspellings with a reference to the standard forms.